2017
DOI: 10.1007/s00792-017-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial and archaeal communities during the concentration of brine at the graduation towers in Ciechocinek spa (Poland)

Abstract: This study evaluates the changes in bacterial and archaeal community structure during the gradual evaporation of water from the brine (extracted from subsurface Jurassic deposits) in the system of graduation towers located in Ciechocinek spa, Poland. The communities were assessed with 16S rRNA gene sequencing (MiSeq, Illumina) and microscopic methods. The microbial cell density determined by direct cell count was at the order of magnitude of 107 cells/mL. It was found that increasing salt concentration was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
4
9
0
Order By: Relevance
“…Members of this genus are characterized by sharing many features with archaeal cells of the family Halobacteriaceae that live in the same habitat [48]. The Psychroflexus (phylum Bacteroidota) genus has also been described in saline environments, including marine solar salterns and graduation towers [49,50]. Little is known about the "Candidatus Aquiluna" genus (phylum Actinobacteria).…”
Section: Taxonomic Profilesmentioning
confidence: 99%
“…Members of this genus are characterized by sharing many features with archaeal cells of the family Halobacteriaceae that live in the same habitat [48]. The Psychroflexus (phylum Bacteroidota) genus has also been described in saline environments, including marine solar salterns and graduation towers [49,50]. Little is known about the "Candidatus Aquiluna" genus (phylum Actinobacteria).…”
Section: Taxonomic Profilesmentioning
confidence: 99%
“…The diversity indices obtained from the salterns of Goa were comparable against the diversity of similar thalassohaline ecosystems like solar salterns located in USA (Youssef et al, 2012), India (Sen and Mukhopadhyay, 2019), Turkey (Çinar and Mutlu, 2016), and Spain (Gómez-Villegas et al, 2018), soda ash concentration ponds in Ethiopia (Simachew et al, 2016) and graduation towers from Poland (Kalwasińska et al, 2018). When the diversity between the two salt production phases was compared, samples from the ISH phase indicated an overall higher diversity owing to the moderately halophilic and halotolerant regime prevailing before the start of the salt production process.…”
Section: Coastal Salterns Of Siridao Are One Of the Most Diverse Solamentioning
confidence: 57%
“…The prevalence of Haloquadratum, a cosmopolitan halophilic archaeal genus in the crystallizer pans around the world (Maturrano et al, 2006;Baati et al, 2011;Ghai et al, 2011;Dillon et al, 2013) was found to be negligible (<0.3% of available reads) in Siridao salterns. Few studies have also reported the low or negligible occurrence of Haloquadratum in salterns that are very similar in operation with Siridao salterns and other hypersaline environments (Pašić et al, 2005;Wang et al, 2007;Manikandan et al, 2009;Kalwasińska et al, 2018). This may be explained by the lower level of magnesium prevalent in the saltern samples.…”
Section: Halophilic Archaea Tolerate Wide Salinity Fluctuations and Smentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of chlorides on the body during bath (osmotic) or inhalation (increasing the secretion and fluidity of mucus) are because of their reaction with sodium ions [17]. Brines are concentrated salt (sodium chloride waters) solutions, which occur widely in natural forms such as coastal lagoons, salt or soda lakes, deep-sea brines, groundwater, and salterns or saltworks of anthropogenic origin [14]. A graduation tower is a unique structure that is used to produce salt; it removes water from a saline solution by evaporation, thereby increasing the concentration of mineral salts.…”
Section: Characteristics Of Natural Medicinal Watersmentioning
confidence: 99%